Proximate analysis of condensed fish solubles and ethanol extractives prepared from scoliodon palasorrah cuvier. - Lapie, Lustina P. (College of Fisheries, University of the Philippines, 1974)
The analyses of the percent protein, amino acids, ash, totalk solids, moisture and saponification and iodine members of fats were done using samples of condensed fish solubles and ethanol extractives prepared from Scoliodon Plasorrah cuvier. Results show that the samples have a percentage protein of 12%. Amino acid components of condensed fish solubles were determined using descending paper chromatography. Three standard amino acids were used, Rf values of the amino acids from condensed fish solubles corresponded to cysteine and methionine. The fat extract has an average saponification number of 330.72 and an iodine number of 38.40. Determination of percentage ash shows that the samples contain 6.45% ash. The samples contain also 59.5% moisture and 40.5% total solid.